Outcomes of neonatal congenital diaphragmatic hernia in a non-ECMO center in a middle-income country: a retrospective cohort study - Lucy Chai See Lum; Tindivanum Muthurangam Ramanujam; Yee Ian Yik; Mei Ling Lee; Soo Lin Chuah; Emer Breen; Anis Siham Zainal-Abidin; Srihari Singaravel; Conjeevaram Rajendrarao Thambidorai; Jessie Anne de Bruyne; Anna Marie Nathan; Surendran Thavagnanam; et al. (BMC, 2022)
Abstract Background Most studies examining survival of neonates with congenital diaphragmatic hernia (CDH) are in high-income countries. We aimed to describe the management, survival to hospital discharge rate, and factors associated with survival of neonates with unilateral CDH in a middle-income country. Methods We retrospectively reviewed the medical notes of neonates with unilateral CDH admitted to a pediatric intensive care unit (PICU) in a tertiary referral center over a 15-year period, from 2003-2017. We described the newborns' respiratory care pathways and then compared baseline demographic, hemodynamic, and respiratory indicators between survivors and non-survivors. The primary outcome measure was survival to hospital discharge. Results Altogether, 120 neonates were included with 43.3% (52/120) diagnosed antenatally. Stabilization occurred in 38.3% (46/120) with conventional ventilation, 13.3% (16/120) with high-frequency intermittent positive-pressure ventilation, and 22.5% (27/120) with high frequency oscillatory ventilation. Surgical repair was possible in 75.0% (90/120). The overall 30-day survival was 70.8% (85/120) and survival to hospital discharge was 66.7% (80/120). Survival to hospital discharge tended to improve over time (p > 0.05), from 56.0% to 69.5% before and after, respectively, a service reorganization. For those neonates who could be stabilized and operated on, 90.9% (80/88) survived to hospital discharge. The commonest post-operative complication was infection, occurring in 43.3%. The median survivor length of stay was 32.5 (interquartile range 18.8-58.0) days. Multiple logistic regression modelling showed vaginal delivery (odds ratio [OR] = 4.8; 95% confidence interval [CI] [1.1-21.67]; p = 0.041), Apgar score $$\ge$$ ≥ 7 at 5 min (OR = 6.7; 95% CI [1.2-36.3]; p = 0.028), and fraction of inspired oxygen (FiO2) < 50% at 24 h (OR = 89.6; 95% CI [10.6-758.6]; p < 0.001) were significantly associated with improved survival to hospital discharge. Conclusions We report a survival to hospital discharge rate of 66.7%. Survival tended to improve over time, reflecting a greater critical volume of cases and multi-disciplinary care with early involvement of the respiratory team resulting in improved transitioning from PICU. Vaginal delivery, Apgar score $$\ge$$ ≥ 7 at 5 min, and FiO2 < 50% at 24 h increased the likelihood of survival to hospital discharge.